2006
DOI: 10.1115/1.2718234
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Soot Formation Model for 3D Diesel Engine Simulations

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
17

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 27 publications
2
19
0
17
Order By: Relevance
“…We also found that while the dominant contribution to the CPU-time spent overall still stems from solving the chemical kinetic equations, solving the population balance can reach about the same computational cost. Experimental results of this study, as well as findings in the literature [14], suggest that aggregates recirculated in exhaust gases play an important role, as described in more detail below, which we substantiated by preliminary simulations. For this reason, we decided to conduct all our simulations over ten consecutive cycles, starting with trapped residuals with typical gas-phase composition, but not containing any soot.…”
Section: Simulations Results and Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…We also found that while the dominant contribution to the CPU-time spent overall still stems from solving the chemical kinetic equations, solving the population balance can reach about the same computational cost. Experimental results of this study, as well as findings in the literature [14], suggest that aggregates recirculated in exhaust gases play an important role, as described in more detail below, which we substantiated by preliminary simulations. For this reason, we decided to conduct all our simulations over ten consecutive cycles, starting with trapped residuals with typical gas-phase composition, but not containing any soot.…”
Section: Simulations Results and Discussionsupporting
confidence: 63%
“…More recently, the focus has still remained on phenomenology and on using descriptions based on only a small number of quantities, although improvements have been made [14][15][16]. In [17], three empirical soot models of varying complexity implemented in KIVA are reviewed and compared.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the models are obviously advantageous because they include particle dynamics, being able to predict the sizes and the number density of soot particles formed in engines. Given the speculation that the forthcoming emissions regulation will soon impose a measure on the number and size of tailpipe PMs, the MSP modeling approach continues to receive renewed attention (e.g., [9]). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the numerical studies on the pollutants formation prediction have been performed in order to improve the predictive capability of models for engine simulations. Boulanger et al [29,30] have developed an improved phenomenological soot model for 3D multi-dimensional engine simulations. Guo et al [31] have analyzed the interaction between soot and NO x formation, and the results show that the influence of soot on NO formation is caused by not only the radiationinduced thermal effect, but also the reaction-induced chemical effect.…”
Section: Introductionmentioning
confidence: 99%